The Development of Enrichment Book of Writing Negotiation Texts: The 21st Century’s Competencies of Senior High School Students - Rofingah, Rofingah; Zulaeha, Ida; Wagiran, Wagiran (Universitas Negeri Semarang, 2020)
The enrichment book is one of the supporting tools of learning activities directed in developing of students’ knowledge, insights, and skills. The purpose of this research is to describe the profile and acceptability of the development of enrichment book in writing negotiation texts based on the 21st century’s competencies that are in appropriate with the students’ and educators’ needs. This research was conducted by seven stages that used a research and development design. The seven stages are (1) potential and problems, (2) information and data collection, (3) design of book’s profile, (4) validation test (5) revision (6) limited trial, and (7) final revision. The result of this research is a development of enrichment book for writing negotiation texts that is compiled with 21st century’s competencies (4C) which is directed at 21stcentury learning. The negotiation text that is developed contains of the 21st century’s competencies aspects, namely critical-thinking, creative, communicative, and collaborative. The acceptability of enrichment books for educators and students is an enrichment book that helps them understand and increase their knowledge of the materials in writing negotiation texts, and the presentation of enrichment book is adjusted to students’ characteristics and their development level. The theoretical benefits of this research can be used as an alternative theory in developing an enrichment book that is customized to the need of 21st century’s students. The practical benefit can be used as a guide-book for the educators.